Development and Application of a Water Temperature Related Physiologically Based Pharmacokinetic Model for Enrofloxacin and Its Metabolite Ciprofloxacin in Rainbow Trout - Yang, Fan; Yang, Fang; Wang, Dan; Zhang, Chao-Shuo; Wang, Han; Song, Zhe-Wen; Shao, Hao-Tian; Zhang, Mei; Yu, Meng-Li; Zheng, Yang (Frontiers in Veterinary Science, 2021)
Enrofloxacin (ENR) was approved in aquaculture to treat infections but could result in tissue residues. This study aimed to develop and validate a water temperature related PBPK model, including both ENR and ciprofloxacin (CIP), in rainbow trout, and to predict further their residue concentrations and the withdrawal periods for ENR at different water temperatures. A flow-limited PBPK model, including both ENR and CIP sub-models, was developed with published data using acslXtreme. This model predicted ENR and CIP concentrations in tissues and plasma/serum after intravenous, oral, or immersion administration. A Monte Carlo simulation, including 500 iterations, was also incorporated into this model. Based on the model and Monte Carlo analysis, the withdrawal intervals were estimated for different dosage regimens and at different water temperatures, ranging from 80 to 272 degree-days. All of these values were shorter than the labeled withdrawal period (500 degree-days) in fish. This model provides a useful tool to predict tissue residues of ENR and CIP in rainbow trout under different dosage regimens and at different water temperatures.